Computational Fluid Dynamics Analysis into The Improvement of Seakeeping Characteristics of A Fast Craft Using AXE-Bow - Romadhoni, Romadhoni; Utama, IKAP; Li, Binbin (IPTEK Journal of Proceedings Series, 2015)
It is obviously understood that hull shape affects the movement characteristics and operability of a ship. There are several ways which can be conducted in order to improve the operability of a ship one of those is by improving ship bow. Recent development known as AXE-Bow was introduced by Delft University of Technology in collaboration with DAMEN Shipyard, in the Netherlands. It was reported that the AXE-Bow can improve the seakeeping characteristics of the vessel at higher speed (Froude number above 0.60), such as reduce vertical acceleration. The current work is carried out numerically using Computational Fluid Dynamics (CFD) approach together with the use of CFD code called Hydrostar provided by Bureau Veritas (BV). The overall results showed that there are good agreement between CFD method and the work by Delft University of University and DAMEN Shipyard. Comparative studies were also carried out with published data and demonstrated similar findings